Modification, Characterization of Tea Residue-derived Activated Carbon, and Ciprofloxacin Adsorption - Kareem Mohammed, Alaa; M. Rashid, Israa M.; AL Sbani, Nadya; Wan Isaha, wan (Al-Khwarizmi Engineering Journal, 2024)
Tea residue was used for preparing activated carbon (AC) which was used as an adsorbent to remove Ciprofloxacin (CIP) from synthetic contaminated water. This study investigates the physicochemical properties and adsorption efficiency of the prepared activated carbon. The activated carbon was prepared via two steps: Activation step using phosphoric acid (H3PO4) followed by carbonization at a temperature of 450 °C.  Different factors were investigated to show their effects on the adsorption efficiency of (CIP). These factors were initial concentration of (CIP), pH, Absorption time, and adsorbent dosage. The maximum adsorption efficiency was 94.4% which was obtained when pH=8.75, contact time =454 min, adsorbent dosage =0.194 g/ 25 ml, and initial concentration of 200 ppm. The prepared activated carbon was characterized using Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), X-ray diffraction (XRD), and Brunauer-Emmett-Teller (BET). The prepared activated carbon was found to have a specific surface area of 774 m2/g. It was found that the Langmuir model well fit the adsorption isotherm of (CIP) on the prepared activated carbon. The produced activated carbon can adsorb Ciprofloxacin, with a maximum adsorption capacity of 256.41 mg g-1. A pseudo-second-order reaction model is effective at describing the kinetics of adsorption. The examination of adsorption thermodynamics reveals that the process of CIP adsorption on TAC is characterized by being both endothermic and spontaneous.